Maternal Education and Diarrhea among Children aged 0-24 Months in Nigeria (2017)
Childhood diarrhea remains a problem in countries like Nigeria where access to potable water, good hygiene and sanitation are lacking. Maternal education is an important determinant of health status of under-five children. Very few studies have investigated the relationship between maternal education and diarrhea in children in Nigeria. Therefore, this study was implemented to fill the gap. The study design was cross-sectional and 2013 National Survey was used. Children aged 0-24 months were investigated and the dependent variable was diarrhea status of the index child in the last two weeks prior the survey. The main independent variable was maternal education. Data were analyzed using Chi-square and Logistic regression models (α=0.05). Diarrhea prevalence was 13.7% and higher (15.5%) among children of women who have no formal education, and mothers living in the North East region of Nigeria experienced the highest prevalence (26.4%). Children whose mothers had no formal education were 2.69(CI= 1.800-4.015, p<0.001) more likely to have diarrhea as compared to those who had higher education. Maternal education is an important predictor of diarrhea among children aged 0-24 months in Nigeria. Policies to reduce diarrhea among children in Nigeria should target children of the illiterate, less educated mothers and those living in the North-West.